CASH FLOW ANALYSIS IN INVESTMENT ACTIVITIES - Abduvohidov, Eldor (Science technology&Digital finance, 2023)
This article describes the meaning and essence of investment, investment activities, how investment financial flow is formed, how investment cash flow is calculated, and the use of cash flows in various ways of evaluating an investment project.